The design for therapeutic agents of Leucine Rich Repeat protein using bioinformatics - 김성열; 박범석 (International Journal of Advanced Culture Technology(IJACT), 2019)
Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by progressive joint deterioration; Furthermore, RA can also affect body tissues, including the skin, eyes, lungs, heart and blood vessels. The early stages of RA can be difficult to diagnose because the signs and symptoms mimic those of many other diseases. It is not known exactly what triggers the onset of RA and how to cure the disease. But recent discoveries indicate that remission of symptoms is more likely when treatment begins early with strong medications known as disease-modifying anti-rheumatic drugs (DMARDs). Tumor necrosis factor (TNF) inhibitors are typical examples of biotherapies that have been developed for RA. The substances may occur naturally in the body or may be made in the laboratory. Other biological therapies care biological response modifiers (BRMs) such as monoclonal antibodies, interferon, interleukin-2 (IL-2) and a protein binder using repeat units. These substances play significant anti-inflammatory roles. Proteins with recurrent, conserved amino acid stretches mediate interactions among proteins for essential biological functions; for example, ankyrin (ANK), Heat repeat protein (HEAT), armadillo repeat protein (ARM) and tetratricopeptide repeats (TPR). Here, we describe Leucine rich repeats (LRR) that ideally fold together to form a solenoid protein domain and is more applicable to our current study than the previously mentioned examples. Although BRMs have limitations in terms of immunogenicity and effector functions, among other factors, in the context therapeutic use and for proteomics research, We has become clear that repeat-unit-derived binding proteins will increasingly be used in biotechnology and medicine.